Comparative Efficacy of Alpha Guard and Formalin Fumigation in Reducing Microbial Contamination in Operation Theater: A Pre- and Post-Intervention Cross-Sectional Analysis from a Tertiary Care Hospital (Journal of Medical & Health Sciences Review, 2025)
Background: Microbial contamination in operation theaters (OT) represents a critical risk factor for surgical site infections (SSIs) and adverse patient outcomes. Chemical fumigation using formalin and newer agents like Alpha Guard are employed for environmental decontamination, but comparative effectiveness data remain limited in tertiary care settings.Objective: This study compared the efficacy of Alpha Guard and formalin fumigation in reducing microbial contamination in operation theaters using pre- and post-intervention microbial sampling.Methods: A cross-sectional comparative study was conducted in a 600-bed tertiary care hospital. Pre-fumigation and post-fumigation microbial samples (n=240) were collected from five operation theaters over 12 weeks. Sampling locations included air, surfaces, and equipment. Colony-forming units (CFU) were enumerated and identified using standard microbiological techniques. Data were analyzed using SPSS v27.0 with paired t-tests, independent t-tests, and descriptive statistics.Results: Alpha Guard fumigation demonstrated superior microbial reduction compared to formalin across all parameters. Mean CFU reduction in air samples: Alpha Guard 94.2% vs. Formalin 78.3% (p